A importância da intoxicação natural por Amorimia pubiflora (Malpighiacea) em bovinos no estado de Mato Grosso, reprodução experimental da intoxicação em ovinos e bovinos e indução e transferência de resistência a intoxicação por A. pubiflora em ovinos - Becker, Marciel (2013)
Epidemiological aspects of natural poisoning by Amorimia (=Mascagnia) pubiflora, (A. Juss.) W.R. Anderson, in cattle in the county of Colniza, Mato Grosso State, Brazil, and the experimental reproduction of the poisoning in cattle and sheep are described. Young leaves collected during two seasons were administered to sheep and cattle and mature leaves and fruits were administered to sheep and study investigates the induction and transfer of resistance to poisoning by A. pubiflora in sheep. The occurrence of poisoning by A. pubiflora was found in farm visits in 2004, 2011 and 2012 from clinical pathology and the presence of the plant in the pastures.. The poisoning was experimentally reproduced in cattle and sheep. The onset of clinical signs occurred in average 8 hours after administration of the plant and the clinical manifestation period was around 4 hours, with a superacute final phase which ranged from 3 to 21 min. The main clinical signs were tachycardia, engorment of the jugular veins, muscle trembling, apathy and reluctance to move, which were more evident especially when the animals were moved. The young leaves, independently of the collection period, were more toxic and caused death of sheep and cattle after ingestion of 2g/kg and 3g/kg, respectively. Mature leaves caused death at the dose of 20g/kg and the fruits at 5g/kg. Young leaves of A. pubiflora contained 0,015% of sodium monofluoracetate, which is responsible for clinical signs of “sudden death”. The resistance to consumption was induced by daily during 20 days at a dose of 0.5 g / kg A. pubiflora for a Group of Sheep (G1-i)after an interval of 15 days were challenged with a dose of 1g/kg for 3 consecutive days. Evaluation the possibility of transfer of resistance with transfaunation of rumen fluid from G1-i to a group of sheep (G2-t) who had no prior contact with A. pubiflora and subsequently challenged similarly to G1-i. The resistance was conferred by clinical monitoring, particularly onset of clinical signs, heart rate, and clinical outcome compared to control groups (GC-1 and GC-2) which have not gone through phases of induction or transfaunation but received dosage toxic plant. Sheep from G1-i and G2-t showed clinical signs ± 58h 17h 51h ± and 101H, respectively, after administration of the plant, the average heart rate was 83 ± 11 and 84 ± 13 beats per minute (bpm), respectively, while the heart rate of GC-1 was 126 bpm and the onset of clinical signs was approximately 23h. Of the five transfaunation recipient sheep, 4 remained alive while all of the control group died when challenged with 3g/kg of leaves of A. pubiflora. The plant is toxic also for sheep causing a clinical picture similar to that reported in cattle poisoned by monofluoracetate-containing plants and The findings indicate that nontoxic doses daily of A. pubiflora (0.075 mg / kg AFM) induce resistance and the resistance can be transmitted by not resistant to transfaunation.